The Role of Regional Government in Managing Legal Aid for the Poor - Bharro Zikrillah al Rasyid; Aviccena Alfajri Firli; Ahmad Yudha Alkautsar (Terekam Jejak Publisher, 2025)
Economic limitations often prevent poor people from getting legal aid when facing legal problems, a social injustice. This paper examines the responsibility of regional government in providing legal aid to this community group. The research method used is a normative legal approach, relying on data from legal literature studies. The conclusion of the study shows that legal aid has a positive impact in increasing the understanding of rights for poor people, especially in the economic field, facilitating access to justice, and encouraging social change towards better welfare in various aspects for all Indonesian people.